2013
DOI: 10.1371/journal.pone.0064223
|View full text |Cite
|
Sign up to set email alerts
|

Highly Upregulated Lhx2 in the Foxn1−/− Nude Mouse Phenotype Reflects a Dysregulated and Expanded Epidermal Stem Cell Niche

Abstract: Hair cycling is a prime example of stem cell dependent tissue regeneration and replenishment, and its regulatory mechanisms remain poorly understood. In the present study, we evaluated the effect of a blockage in terminal keratinocytic lineage differentiation in the Foxn1−/− nude phenotype on the epithelial progeny. Most notably we found a constitutive upregulation of LIM homeobox protein 2 (Lhx2), a marker gene of epithelial stem cellness indispensible for hair cycle progression. However, histological evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Correspondingly, our previous data showed that large populations of nude dermal fibroblasts display stem cell biomarkers compared to wild type B6 dermal fibroblasts [45]. Therefore, we assume that the lack of Foxn1 activity prevents the final stages of differentiation [14] and keeps cells in an immature progenitor-like state [43, 46]. …”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Correspondingly, our previous data showed that large populations of nude dermal fibroblasts display stem cell biomarkers compared to wild type B6 dermal fibroblasts [45]. Therefore, we assume that the lack of Foxn1 activity prevents the final stages of differentiation [14] and keeps cells in an immature progenitor-like state [43, 46]. …”
Section: Resultsmentioning
confidence: 82%
“…In our regenerative models, we detected down-regulation of some transcription factors that promote differentiation and block proliferation of epidermal progeny cells (genes repressed by PcG; Table 1). This can lead to an increase in the number of undifferentiated, presumably epidermal stem cells (ESC) [43]. Previously, it was shown that a local population of ESC exerts a positive impact on skin regenerative capacity [44].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, hair cycling was determined to be functional by the presence of cyclin D1 mRNA in nude mice (52). It is well known that these mice do not produce hair cortex (16) and form an abrogated inner root sheath (IRS) (27).…”
Section: Nude Mice (Foxn1 Deficient) From the Skin Point Of Viewmentioning
confidence: 99%
“…There were reported differences in the distribution of SC/progenitor fractions in HFs of nude mice versus wild-type controls. The stem cell markers SOX2 (sex-determining region Y [SRY] box 2) and OCT4 (octamer-binding transcription factor 4) are downregulated, in contrast to the upregu- lation of LHX2 (LIM homeobox protein 2), which is responsible for anagen progression, and the Wnt signaling target gene, ␤-catenin, which is uniformly expressed at high levels in the nude mice (52). Similarly, in spiny mice, which are another case of mammals able to regenerate their tissues, the readout of Wnt inductive signaling, LEF1, was present at high levels in both epidermal and dermal cells of forming hair placodes (53).…”
Section: Nude Mice (Foxn1 Deficient) From the Skin Point Of Viewmentioning
confidence: 99%
See 1 more Smart Citation